Experimental Economics Volume II: Economic Applications - Branas-Garza, Pablo; Cabrales, Antonio (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
How do applications affect behavior? Experimental Economics Volume II seeks to answer these questions by examining the auction mechanism, imperfect competition and incentives to understand financial crises, political preferences and elections, and more.